The Impact of Thin-Capitalization Rules on External Debt Usage: A Propensity Score Matching Approach - Georg Wamser (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2008)
This paper analyzes how multinational enterprises respond to a restriction on interestdeductions incurred for internal borrowing. The emphasis of the study is on a firmsresponse with respect to external borrowing. The empirical investigation appliespropensity score matching techniques and exploits the 2001 reform of the German thin-capitalizationrule to solve endogeneity problems. The results suggest that restrictionson internal debt are associated with expansions in external debt finance, indicating asubstitutional relationship. Since multinational enterprises can use internal debt to shiftprofits from high- to low-tax countries, this finding implies that policies aimed atsecuring corporate tax revenue possibly fail and should be subject to careful scrutiny bypolicymakers.
Keywords: G32; H25; 330